A joint theoretical and kinetic investigation on the fragmentation of (N-halo)-2-amino cycloalkanecarboxylates - Queralt, Joaquim J; Andrés, Juan; M.C., MoiseCanle; Hermógenes Cobas, J.; Santaballa, Juan A; Sambrano, Julio R [UNESP] (Elsevier, 2002)
A combined theoretical and experimental study to elucidate the molecular mechanism for the Grob fragmentation of different (N-halo)-2-amino cyclocarboxylates with the nitrogen atom in exocyclic position: (N-Cl)-2-amino cyclopropanecarboxylate (1), (N-Cl)-2-amino cyclobutanecarboxylate (2), (N-Cl)-2-amino cyclopentanecarboxylate (3) and (N-Cl)-2-amino cyclohexanecarboxylate (4), and the corresponding acyclic compounds, (N-Cl)-2-amino isobutyric acid (A), (N-Cl)-2-amino butyric acid (B), has been carried out. The kinetics of decomposition for these compounds and related bromine derivatives were experimentally determined by conventional and stopped-flow UV spectrophotometry. The reaction products have been analyzed by GC and spectrophotometry. Theoretical analysis is based in the localization of stationary points (reactants and transition structures) on the potential energy surface. Calculations were carried out at B3LYP/6-31+G* and MP2/6-31+G* computing methods in the gas phase, while solvent effects have been included by means the self-consistent reaction field theory, PCM continuum model, at MP2/6-31+G* and MP4/6-31+G*//MP2/6-31+G* calculation levels. Based on both experimental and theoretical results, the different Grob fragmentation processes show a global synchronicity index close to 0.9, corresponding to a nearly concerted process. At the TSs, the N-Cl bond breaking is more advanced than the C-C cleavage process. An antiperiplanar configuration of these bonds is reached at the TSs, and this geometrical arrangement is the key factor governing the decomposition. In the case of 1 and 2 the ring strain prevents this spatial disposition, leading to a larger value of the activation barrier. Natural population analysis shows that the polarization of the N-Cl and C-C bonds along the bond-breaking process can be considered the driving force for the decomposition and that a negative charge flows from the carboxylate group to the chlorine atom to assist the reaction pathway. A comparison of theoretical and experimental results shows the relevance of calculation level and the inclusion of solvent effects for determining accurate unimolecular rate coefficients for the decomposition process. © 2002 Published by Elsevier Science B.V.
Keywords: alkane; bromine derivative; carboxylic acid derivative; cyclopropane derivative; nitrogen; calculation; chemical bond; chemical reaction kinetics; decomposition; gas; gas chromatography; polarization; surface property; ultraviolet spectrophotometry